Global REACH 2018: Influence of excessive erythrocytosis on coagulation and fibrinolytic factors in Andean highlanders. Issue 6 (27th April 2021) - DeSouza, Noah M.; Brewster, L. Madden; Bain, Anthony R.; Garcia, Vinicius P.; Stone, Rachel; Stockelman, Kelly A.; Greiner, Jared J.; Tymko, Michael M.; Vizcardo‐Galindo, Gustavo; Figueroa‐Mujica, Romulo J.; Villafuerte, Francisco C.; Ainslie, Philip N.; et al.
Abstract : New Findings: What is the central question of this study? Are coagulation and fibrinolytic factors disrupted in Andean highlanders with excessive erythrocytosis? What is the main finding and its importance? Excessive erythrocytosis is not associated with prothombotic disruptions in coagulation or the fibrinolytic system in Andean highlanders. Impairments in coagulation and fibrinolysis may not contribute to the increased vascular risk associated with excessive erythrocytosis. Abstract: Increased coagulation and reduced fibrinolysis are central factors underlying thrombotic risk and events. High altitude‐induced excessive erythrocytosis (EE) is prevalent in Andean highlanders, contributing to increased cardiovascular risk. Disruption in the coagulation–fibrinolytic axis resulting in uncontrolled fibrin deposition might underlie the increased thrombotic risk associated with high‐altitude EE. The experimental aim of this study was to determine whether EE is associated with a prothrombotic blood coagulation and fibrinolytic profile in Andean highlanders. Plasma coagulation factors (von Willebrand factor and factors VII, VIII and X), fibrinolytic factors [tissue‐type plasminogen activator (t‐PA) and plasminogen activator inhibitor‐1 (PAI‐1)] and D‐dimer levels were determined in 26 male residents of Cerro de Pasco, Peru (4340 m a.s.l.): 12 without EE (age, 40 ± 13 years; haemoglobin, 17.4 ± 1.9 g/dl) and 14 with EE (age, 43 ± 15 years; haemoglobin, 24.4 ± 1.6 g/dl). There were no significant differences in von Willebrand factor (40.5 ± 24.8 vs. 45.5 ± 22.4%), factor VII (77.0 ± 14.5 vs. 72.5 ± 8.9%), factor VIII (55.6 ± 19.8 vs. 60.7 ± 26.8%) and factor X (73.9 ± 8.3 vs. 67.3 ± 10.9%) between the Andean highlanders without or with EE. The t‐PA antigen (8.5 ± 3.6 vs. 9.6 ± 5.4 ng/ml), t‐PA activity (5.5 ± 2.4 vs. 5.8 ± 1.6 IU/ml), PAI antigen (45.0 ± 33.8 vs. 40.5 ± 15.8 ng/ml), PAI‐1 activity (0.24 ± 0.09 vs. 0.25 ± 0.11 IU/ml) and the molar concentration ratio of active t‐PA to active PAI‐1 (1:0.051 ± 0.034 vs. 1:0.046 ± 0.021 mmol/l) were also similar between the groups, as were D‐dimer levels (235.0 ± 126.4 vs. 268.4 ± 173.7 ng/ml). Collectively, the results of the present study indicate that EE is not associated with a hypercoagulable, hypofibrinolytic state in Andean highlanders. Abstract :